Cambridge FCE Practice Tests 2. For the Cambridge English: First for Schools Examination - Stephens N. Nicholas (Oxford, Hamilton House Publishers, 2015)
Cambridge First Certificate Practice Tests 1 has been specifically written for the updated Cambridge English: First for Schools Examination. The tests have been designed to familiarise students with the exact format of the new examination as well as to expand their vocabulary and to improve the skills required the examination.